Pengamanan Data Akademik Berbasis Web dengan Enkripsi AES-256 (Studi Kasus pada Pendataan Digital SMA XYZ) - Zahrah Hayat Arka Putri; Yessy Arye Yustraini; Ramdhan Ariansyah; Najma Choirun Nisa; Eka Dyar Wahyuni; Agung Brastama Putra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The advancement of information technology has significantly facilitated data management, particularly in the field of education. However, this convenience also presents new challenges in ensuring data security, especially for academic information that is sensitive and vulnerable to unauthorized access. This study aims to develop a web-based academic data security system by implementing the AES-256 encryption algorithm in Cipher Block Chaining (CBC) mode. The system is built using the PHP programming language and MySQL database to manage student data such as name, NISN, class, address, gender, religion, and mother’s name. The core functionality lies in encrypting and decrypting sensitive information using the openssl_encrypt and openssl_decrypt functions, integrated with a 256-bit encryption key and a randomly generated Initialization Vector (IV) to ensure confidentiality. The encrypted data is stored in base64 format to maintain compatibility with relational databases and storage systems. Testing was conducted to evaluate the accuracy of the encryption-decryption process and to assess the impact on system performance. Results show that the system effectively secures sensitive data; the encrypted entries in the database are unreadable to unauthorized users and can only be restored using the correct encryption key and IV. With a simple yet functional user interface and automated encryption handling, the system proves to enhance academic data security without compromising operational efficiency. These findings demonstrate that the implementation of AES-256-CBC encryption can be effectively applied in educational information systems, offering a practical and reliable solution for safeguarding academic data in web-based environments.